2022
DOI: 10.1186/s12889-022-13201-0
|View full text |Cite
|
Sign up to set email alerts
|

Young people in Australia discuss strategies for preventing the normalisation of gambling and reducing gambling harm

Abstract: Background The normalisation of gambling for young people has received considerable recent attention in the public health literature, particularly given the proliferation of gambling marketing aligned with sport. A range of studies and reports into the health and wellbeing of young people have recommended that they should be consulted and engaged in developing public health policy and prevention strategies. There are, however, very few opportunities for young people to have a say about gambling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
(65 reference statements)
0
16
0
Order By: Relevance
“…Children aged 8 to 17 years (and their parents) have recommended gambling harm prevention strategies that are consistent with public health approaches, including advertising restrictions, campaigns about gambling risks, untangling gambling from sport and restricting gambling availability in community settings. 7,32 A recent study also found that there was support to address gambling risks and harms among gamblers including young men who belonged to sporting clubs. 33 However, few studies have sought to understand similar perspectives from young men aged 18 to 24 years, who are classified as young people, but are legally permitted to gamble in Australia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children aged 8 to 17 years (and their parents) have recommended gambling harm prevention strategies that are consistent with public health approaches, including advertising restrictions, campaigns about gambling risks, untangling gambling from sport and restricting gambling availability in community settings. 7,32 A recent study also found that there was support to address gambling risks and harms among gamblers including young men who belonged to sporting clubs. 33 However, few studies have sought to understand similar perspectives from young men aged 18 to 24 years, who are classified as young people, but are legally permitted to gamble in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Young people have been consulted in other areas of public health, including in the design of service and policy initiatives for mental health 28,29 . Creating structures that engage young people in the development of public health policies have been recommended by The Lancet Commission on Adolescent Health and Wellbeing and The WHO‐UNICEF‐Lancet Commission “A Future for the World's Children?” 30,31 The Lancet Commission on Adolescent Health and Wellbeing 29 stated that:
“… adolescents and youth should be supported and empowered to contribute to designing, implementing and assessing policies, programs and systems that contribute to their health and wellbeing ” (p. 34).
The WHO‐UNICEF‐Lancet Commission report 30 argued that young people have the:
“… right to be involved in decisions and actions that affect them, to be able to express their views, which are then duly recognised by adults ” (p. 616).
Children aged 8 to 17 years (and their parents) have recommended gambling harm prevention strategies that are consistent with public health approaches, including advertising restrictions, campaigns about gambling risks, untangling gambling from sport and restricting gambling availability in community settings 7,32 . A recent study also found that there was support to address gambling risks and harms among gamblers including young men who belonged to sporting clubs 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite not being impacted by the climate crisis on a day-to-day basis, children in this study demonstrated a high level of consideration and empathy for the circumstances and challenges faced by others. Empathy in children and young people can be observed across other studies relating to climate ( Hickman et al ., 2021 ), as well as in other public health issues such as gambling ( Pitt et al ., 2022 ). Research shows that adults’ personal experiences of the climate crisis influences their strength of belief and opinion about the need for climate mitigation ( Weber, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…These approaches continue to dominate. Studies show that stakeholders endorse a range of evidence‐based strategies that seek to denormalise the gambling industry, and focus on the problematic nature of products, rather than ‘personal responsibility’ messages 8,36,37 …”
mentioning
confidence: 99%
“…Studies show that stakeholders endorse a range of evidence-based strategies that seek to denormalise the gambling industry, and focus on the problematic nature of products, rather than 'personal responsibility' messages. 8,36,37 How then can we utilise information about gamblers' attitudes about the link between gambling and Australian culture, along with evidence about strategies from other areas of public health, to develop more effective denormalisation strategies in gambling? Focusing on regular sports and EGM gamblers (those who gambled at least monthly), this study aimed to explore two markers of gambling normalisation -social acceptance and cultural accommodation.…”
mentioning
confidence: 99%